2021
DOI: 10.1093/ser/mwab040
|View full text |Cite
|
Sign up to set email alerts
|

Finance as a friend, enemy and stranger in the US Economy, 1952–2019

Abstract: This article aimed to illustrate that the role of the finance sector in an economic system can be explained more systemically and systematically in the context of its interaction with macroeconomic governance, based on the case of the USA from 1952Q1 to 2019Q2. The article introduced two modes of economic governance based on negative and positive institutional complementarities, developed its hypotheses built on a structural analysis of the long-run relationship between the finance sector and macroeconomic gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…Studies that investigated individual countries concluded in favour of unidirectional causality (Asteriou & Price, 2000; Yang & Yi, 2008), while others that used more than one country found bi‐directional causality (Demetriades and Hussein, 1996). When VAR, VECM or ARDL models were employed, the conclusions were in favour of a positive effect of financial development on growth (Ang & McKibbin, 2007; Arestis et al, 2001), while considering the period of the GFC findings indicated that financial development enhanced and impaired economic performance, in the period before and after the crisis, respectively (Akan et al, 2021). In a recent study, Barradas (2020) examined the relative importance of banks and stock markets in contributing to economic growth and found that stock markets are more powerful in promoting growth than money markets.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies that investigated individual countries concluded in favour of unidirectional causality (Asteriou & Price, 2000; Yang & Yi, 2008), while others that used more than one country found bi‐directional causality (Demetriades and Hussein, 1996). When VAR, VECM or ARDL models were employed, the conclusions were in favour of a positive effect of financial development on growth (Ang & McKibbin, 2007; Arestis et al, 2001), while considering the period of the GFC findings indicated that financial development enhanced and impaired economic performance, in the period before and after the crisis, respectively (Akan et al, 2021). In a recent study, Barradas (2020) examined the relative importance of banks and stock markets in contributing to economic growth and found that stock markets are more powerful in promoting growth than money markets.…”
Section: Literature Reviewmentioning
confidence: 99%